Nutritional and medicinal values of common green leafy vegetables consumed in Delta State, Nigeria: a review - Dada, Taiwo Esther; Otitoloju, Kekere; Adjonu, Randy; Crockett, Judith; Nwose, Ezekiel Uba (International Journal Of Community Medicine And Public Health, 2021)
Green leafy vegetables (GLVs) play an important role in human nutrition. In sub-Saharan African countries, GLVs are a vital source of essential micronutrients, and their consumption has long been a part of the cultural heritage of African households. In Nigeria, GLVs are either cooked as a stew or consumed raw and used as a main or a supporting dish. These GLVs have great nutritional and medicinal value. It is hypothesized that providing knowledge about the botanical description, nutritional and medicinal benefits to consumers could improve consumption, but much of existing knowledge is poorly documented and inaccessible. This paper aims to address this gap by collating information on some consumed in Delta State, Nigeria: African jointfir (Gnetum africanum, locally known as Ukazi), jute mallow, (Corchorus olitorius, locally known as Malafiya), and cassava (Manihot esculenta, Crantz), giant yellow mulberry (Myrianthus arboreus), okra (Abelmoschus esculentus), clove (Syzygium aromaticum) and bush buck, (Gongronema latifolium, locally known as Utazi) leaves.